Association between personality traits and suicidality by age groups in a nationally representative Korean sample. Issue 16 (April 2020) - Na, Kyoung-Sae; Cho, Seo-Eun; Hong, Jin Pyo; Lee, Jun-Young; Chang, Sung Man; Jeon, Hong Jin; Cho, Seong-Jin
Abstract : Abstract: Suicide is a leading health issue, which substantially contributes to the causes of death worldwide. Personality traits are some of the major risk factors for suicidality. We sought to identify the relationships between personality traits and suicidality by age group. The Big-Five Inventory-10 traits were measured in community-dwelling individuals in a nationally representative sample in the Republic of Korea. Because personality traits are long-standing patterns throughout one's lifetime, suicidality was measured based on lifetime history, rather than in a recent period. To comprehensively examine independent influences of personality traits on suicidality, psychiatric comorbidity and sociodemographic data were adjusted for. A total of 6022 subjects (3714 females and 2308 males) were included. Agreeableness (odds ratio (OR) [95% confidential intervals (CI)] = 0.79 [0.64–0.98]) was negatively associated with suicidal ideation, whereas neuroticism (1.27 [1.05–1.54]) and openness (1.36 [1.11–1.67]) were positively associated with suicidal ideation among young adults. Openness (1.25 [1.10–1.43]) had a positive association, and conscientiousness (0.86 [0.75–0.98]) had a negative association with suicidal ideation among the middle-aged group. Neuroticism is the only influencing factor for suicidal attempts among the young adult (1.88 [1.24–2.86]) and older (1.65 [1.24–2.20]) groups. Given the differential associations between personality traits and suicidality by age groups, future studies are needed to comprehensively identify possible roles of personality in suicide by age.